Menstrual and reproductive factors and lung cancer risk: A pooled analysis from the international lung cancer consortium. Issue 2 (10th May 2017) - Ben Khedher, Soumaya; Neri, Monica; Papadopoulos, Alexandra; Christiani, David C.; Diao, Nancy; Harris, Curtis C; Olivo‐Marston, Susan; Schwartz, Ann G.; Cote, Michele; Koushik, Anita; Siemiatycki, Jack; Landi, Maria Teresa; et al.
Abstract : Many clinical features of lung cancer are different in women and men. Sex steroid hormones exert effects in nonreproductive organs, such as the lungs. The association between menstrual and childbearing factors and the risk of lung cancer among women is still debated. We performed a pooled analysis of eight studies contributing to the International Lung Cancer Consortium (4, 386 cases and 4, 177 controls). Pooled associations between menstrual or reproductive factors and lung cancer were estimated using multivariable unconditional logistic regression. Subgroup analyses were done for menopause status, smoking habits and histology. We found no strong support for an association of age at menarche and at menopause with lung cancer, but peri/postmenopausal women were at higher risk compared to premenopausal (OR 1.47, 95% CI 1.11–1.93). Premenopausal women showed increased risks associated with parity (OR 1.74, 95% CI 1.03–2.93) and number of children (OR 2.88, 95% CI 1.21–6.93 for more than 3 children; p for trend 0.01) and decreased with breastfeeding (OR 0.54, 95% CI 0.30–0.98). In contrast, peri/postmenopausal subjects had ORs around unity for the same exposures. No major effect modification was exerted by smoking status or cancer histology. Menstrual and reproductive factors may play a role in the genesis of lung cancer, yet the mechanisms are unclear, and smoking remains the most important modifiable risk factor. More investigations in large well‐designed studies are needed to confirm these findings and to clarify the underlying mechanisms of gender differences in lung cancer risk. Abstract : What's new? Lung cancer has been studied mostly in men, but the disease proceeds very differently in women. Why is that? Evidence suggests that sex‐steroid hormones affect other organs, including the lungs. These authors probed the effect of menstrual and reproductive factors on lung cancer risk using pooled data from 8 different studies involving more than 4, 000 patients. Women who were nearing or past menopause, they found, had increased lung cancer risk compared to premenopausal women. Before menopause, having more children increased one's risk, while breastfeeding decreased it. Although the mechanism is not understood, reproductive factors do appear to affect lung carcinogenesis.